Positive Emotional Traits and Ambitious Goals among People at Risk for Mania: The Need for Specificity - Gruber, June (2009)
Recent psychosocial theories implicate disturbances in reward pursuit among individuals putatively at risk for mania. The present study examined associations of a measure of risk for mania (the Hypomanic Personality Scale; HPS) with both four trait positive emotions (joy, pride, compassion, and love) and ambitious life goals in five domains (fame, wealth, political influence, family, and friends) among 302 participants from two university settings. Findings indicated that higher HPS scores were related to reward (joy) and achievement-focused (pride) positive emotions, with weaker relations to prosocial (compassion, love) positive emotions. HPS scores were more robustly related to extrinsic (fame, politics) as compared to other-oriented (friends, family) ambitious life goals, with the exception of wealth. These effects were independent of current symptoms of mania and depression. Discussion focuses on the implications of elevated reward and achievement-related positive emotions and goals in understanding risk factors for mania.